Moving beyond cognition: An exploration into the metacognitive awareness of science teachers on STEM education - Shifali TV; Maliyakkal, M.N. Mohamedunni Alias Musthafa (Journal of Interdisciplinary Studies in Education, 2024)
Science, technology, engineering, and mathematics (STEM) education has gained popularity as an interdisciplinary approach that combines these subjects into a single curriculum. STEM concepts are in line with the competencies required by the contemporary workforce, making it a desirable education model to foster twenty first-century skills. The dynamism of the metacognitive awareness of science teachers in STEM has not been the subject of serious research. This study explores the metacognitive awareness level of science teachers in STEM, and the results are average. A gap exists between the living culture and the learning culture of students in this digital era. STEM is a new way of learning and comprehending in terms of a sustainable future.